Description of two new genera and two new species of Metarbelidae (Lepidoptera, Cossoidea) from the Northeastern Congolian Lowland Forests Ecoregion (Central Africa) - Lehmann, Ingo (Zootaxa, 2014)
The genera Dianfosseya gen. nov. and Janegoodallia gen. nov. and their single species D. leakeyi sp. nov. and J. davenporti sp. nov. are both described from Isiro, north-eastern Democratic Republic of the Congo, Central Africa (Afrotropical Region). Wing pattern and male genitalia of the new species are depicted and notes on the habitat are presented.